DOES ZAKAT AS AN ISLAMIC SOCIAL FINANCE INSTRUMENT, MAINTAIN PUBLIC PURCHASING POWER? - Fitriani, Fitriani; Wahab, Abd.; Herianingrum, Sri (Universitas Airlangga, 2025)
The decrease in public purchasing power within Indonesian society in 2024 has emerged as a critical issue that may precipitate a broader economic crisis. This study aims to examine the function of zakat in enhancing public purchasing power and fostering economic stability through wealth redistribution. Zakat, as an Islamic social financial mechanism, has the potential to mitigate income inequality by augmenting the financial resources of marginalized groups, thereby increasing their aggregate expenditure. This study utilizes a literature review approach, adhering to the PRISMA model to systematically identify and analyse relevant articles. The findings suggest that productive zakat, which prioritizes economic empowerment through the allocation of business capital and training, exerts a substantial influence on the long-term economic independence of its beneficiaries. Moreover, zakat operates as an automatic stabilizer within the economy, aiding in the maintenance of public purchasing power, particularly during periods of economic strain. This study corroborates the hypothesis that zakat functions as a mechanism for income redistribution and has a multiplier effect that increases demand for goods and services, thereby promoting inclusive economic growth. Therefore, zakat has the potential to function as a strategic solution for enhancing public purchasing power, maintaining economic stability, and strengthening overall socio-economic resilience. Keywords: Zakat, Purchasing Power, Economic Stability, Economic Empowerment, Islamic Economics.